Flouting Maxims Found in "Good Doctor Season 1" - Ni Putu Eka Kumala Niti Utami; Ni Wayan Suastini (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2025)
The study entitled: Flouting Maxims Found in “Good Doctor Season 1” which intends to identify and analyse the different kinds of flouting maxims and the reason in “Good Doctor Season 1” characters use. The data was found in the series entitled Good Doctor Season 1. In this data, the method that is used is observation and analysed in descriptive in qualitative method. This study analysed the flouting maxim in Good Doctor Season 1. This analysis supported by Grice (1975), categorizes the type of flouting maxims. Additionally, Leech (1983) provided theory to justify the rationale behind the characters' employment of the flouting maxims in “Good Doctor Season 1” movie. This study collects 42 pieces of data which flouting maxims; 5 of these were classify as flouting maxims in terms of quality, 8 as flouting maxims in terms of quantity, 22 as flouting maxims in terms of relevance, and 7 as flouting maxims in terms of manner. And this study collects 42 pieces of data on the reason of flouting maxims; 13 pieces of data as competitive, 10 pieces of data as convivial, 9 pieces of data as collaborative, and 10 pieces of data as conflictive. The conclusion of the study states that this movie uses the most relevant maxims and competitive reasoning from 42 data.